The Caine mutiny - Dmytryk, Edward; Bogart, Humphrey, 1899-1957; Ferrer, José, 1912-1992; Johnson, Van, 1916-2008; MacMurray, Fred, 1908-1991 (Columbia TriStar Home Video, 1999)
Η ιστορία αντρών που βιώνουν τις εντάσεις ενός πολέμου μέσα στο ασφυκτικό περιβάλλον ενός πολεμικού πλοίου.